'It reshaped how I will do research': A qualitative exploration of team members' experiences with youth and family engagement in a randomized controlled trial. (15th February 2021) - Sheikhan, Natasha Y.; Hawke, Lisa D.; Cleverley, Kristin; Darnay, Karleigh; Courey, Lynn; Szatmari, Peter; Cheung, Amy; Henderson, Joanna
Abstract: Background: Engaging youth and family members as active partners in research and service design offers great promise in improving projects. In youth mental health, recent research has highlighted the value of youth and family engagement. However, research on the experience and impacts of engagement is sparse. Objective: This study explores the project team's experience of youth and family engagement in the design and development of the YouthCan IMPACT randomized controlled trial and clinical service pathway design. Design: Qualitative data collected using semi‐structured interviews and a focus group as part of the YouthCan IMPACT clinical trial were analysed to understand the impacts of engagement. Twenty‐eight team members were interviewed, including youth and family members. A qualitative content analysis was conducted, with a member checking process. Results: Team members reported facilitators, barriers and impacts of youth and family engagement. Facilitators included a safe environment and strong procedures conducive to inclusion in co‐design. Barriers included logistical, structural and institutional constraints. Overall, team members found youth and family engagement to be valuable and to positively impact the research and service design process. Discussion and Conclusions: Youth and family engagement played a critical role in research and clinical service pathway design. The team found that their involvement improved the quality of the research and service pathway through sustained and multifaceted engagement. Facilitators and barriers to engagement may serve to guide future engagement initiatives. Future research should evaluate the long‐term impact of early engagement and further focus on family engagement. Patient/Public Contribution: Youth and family members were engaged in the data analysis and interpretation process.